The European Court of Human Rights Overwhelmed by Applications:Problems and Possible Solutions - Wolfrum, Rüdiger; Deutsch, Ulrike (Springer-Verlag Berlin Heidelberg, 2009)
A contribution to the discussion on the reform of the control mechanism of the European Court of Human Rights, which is necessary to prevent a failure of the European system of human rights protection
"International workshop, Heidelberg, December 17-18, 2007
Includes bibliographical references
Keywords: European Court of Human Rights -- Congresses; Konferenzschrift -- 2007 -- Heidelberg; Convention for the Protection of Human Rights and Fundamental Freedoms (1950-11-04); Rechtsprechung; Europäischer Gerichtshof für Menschenrechte